Costello Syndrome with Severe Nodulocystic Acne: Unexpected Significant Improvement of Acanthosis Nigricans after Oral Isotretinoin Treatment - Leelawadee Sriboonnark; Harleen Arora; Leyre Falto-Aizpurua; Sonal Choudhary; Elizabeth Alvarez Connelly (Case Reports in Pediatrics)
We report the case of 17-year-old female diagnosed with Costello syndrome. Genetic testing provided a proof with G12S mutation in the HRAS gene since 3 years of age with a presentation of severe nodulocystic acne on her face. After 2 months of oral isotretinoin treatment, improvement in her acne was observed. Interestingly, an unexpected significant improvement of acanthosis nigricans on her neck and dorsum of her hands was found as well. We present this case as a successful treatment option by using oral isotretinoin for the treatment of acanthosis nigricans in Costello syndrome patients.